Abscesos tuberculosos hepáticos en pacientes con síndrome de inmunodeficiencia adquirida (SIDA). - RAEZ, Luis (2013)
We report a AIDS patient with the diagnosis of tuberculous liver abscess. We describe and compare our case with another seven patients reported in the medical literature since AIDS epidemic began. We reviewed the clinical presentations (usually fever and abdominal pain), the diagnositic tests (CT Scanguided needle aspiration or ultrasound) and the outcomes of the treatments. Also we did a review of the current literature available of the types of hepatic compromise related with Mycobacteriun tuberculosis in AIDS patients.